EMOTIONAL INTIMACY IN DANIELLE STEEL'S NOVEL FINE THINGS - Umami, Elvi; Purwarno, Purwarno; Manugeren, M. (Universitas Islam Sumatera Utara, 2024)
This qualitative study delves into the portrayal of emotional intimacy in Danielle Steel's novel, Fine Things using Robert Sternberg's Triangular Theory of Love as a theoretical framework. The research method involved textual analysis of excerpts from the novel, focusing on instances of emotional intimacy depicted among characters. The literature review section provides a comprehensive overview of Sternberg's Triangular Theory of Love, emphasizing its three components: intimacy, passion, and decision/commitment. The analysis highlights the importance of emotional intimacy in various types of relationships, emphasizing its role in fostering closeness, understanding, and trust. The discussion section presents findings from the textual analysis, showcasing excerpts that illustrate the complexities of emotional intimacy among characters in the novel. Examples include moments of vulnerability, communication, and affection shared between romantic partners, family members, and friends. Key findings reveal the nuanced portrayal of emotional intimacy, ranging from expressions of love and support to instances of conflict and betrayal. The conclusion drawn from the analysis underscores the profound impact of emotional intimacy on individuals and their relationships, highlighting its role in shaping the dynamics of love, loss, and personal growth depicted in the novel. Implications of this study extend to a deeper understanding of emotional intimacy in fictional narratives and its relevance to real-life relationships. By applying Sternberg's Triangular Theory of Love to literary analysis, this study contributes to the on-going discourse on the complexities of human emotions and intimate connections portrayed in literature.